Tourism and Education: a systematic review of curriculum and technical education in Tourism - Luis da Silva, Ricardo (REVISTA BRASILEIRA DOS OBSERVATÓRIOS DE TURISMO - ReBOT, 2025)
This work aimed to carry out a bibliographic inquiry, by a systematic review, on the evolution of national and international research in technical education and curriculum in tourism. To achieve this goal, a research was carried out in the Web of Science and Tourism Publications databases, obtaining 15 scientific articles adhered in English, Portuguese and Spanish between 2016 and 2020. The analysis and interpretation of data rooted that most publications on the subject are in applied research, qualitative approach, inductive method, narrative review, descriptive objective, survey procedure, and data collection with questionnaires and interviews. The most frequent subjects studied were education, economics and administration. The main topics covered in the articles were: teaching in tourism; education, professional qualification and training in tourism; construction of tourism curricula.